CITRAAN PADA NOVEL KEMBANG NU DIPITINEUNG KARYA TETY S NATAPRAWIRA - Efrlina Amelia; Fahmi Rakhman (Jurnal Bastra (Bahasa dan Sastra), 2024)
Literary works are created by authors as a way of expressing ideas and thoughts. One form of literary work is a novel. In the novel there are imagery terms described by the author in various forms. The aim of this research is to describe the form of imagery contained in the novel Kembang nu Dipitineung, including: (a) the form of visual imagery;  (b) the form of auditory imagery; (c) form Of movement imagery; and (d) the form of tactile imagery. The research method used is descriptive analysis method with stylistic studies. The data source in this research is primary data, the type of research used is qualitative, the data collection technique used is literature review or literature study. The research results showed that there were 43 forms of visual imagery, 4 forms of auditory imagery, 37 forms of movement imagery, 13 forms of Tactile imagery.